DESKRIPSI PENERAPAN BUKU PERKEMBANGAN BIMBINGAN SKRIPSI DI PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR UNIVERSITAS MATARAM - Radiusman Radiusman; Sukardi Sukardi; Ahmad Helmi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2021)
Undergraduate thesis guidance is one of the most difficult times that all students who wish to complete their studies at college have to go through. The difficulties faced by students include students not writing clearly suggestions from the supervisor, irregular meeting times, and lack of motivation in completing theses. Qualitative descriptive research aims to describe the benefits of using the development book of undergraduate thesis consultant in solving the guidance problems that occur in students. This research was conducted for 6 weeks during basic training activities in the Primary School Teacher Education (PGSD) study program. This research was conducted on 144 students who were conducting undergraduate thesis guidance activities by taking 3 students as research subjects. The data collection technique was done by interviewing. The results of this study indicate that the use of the development book of undergraduate thesis consultant can help students in writing clearly suggestions for improvement, the scheduling of the counseling meeting, and increasing student motivation in completing the undergraduate thesis.